PENGARUH KOMBINASI PENDIDIKAN KESEHATAN DENGAN PRAKTIK PIJAT TERHADAP PERILAKU IBU DALAM MEMIJAT BAYI SENDIRI (USIA 0-1 TAHUN) DI DESA BARATAN KECAMATAN PATRANG KABUPATEN JEMBER - Megawati; Harianah Akib (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
Baby massage is a massage that is done with gentle strokes on the surface of the baby's skin that aims to produce effects on the nerves, muscles, respiratory system and blood circulation and limpha. There are still many wrong habits in doing baby massage, especially in rural communities. Mothers do not dare to do massage alone because they do not have knowledge about baby massage techniques and consider baby massage is not important. The impact of improper baby massage can cause bleeding in the soft tissue and cause a bluish effect on the baby's skin. The purpose of this study was to determine whether there is a combination of health education with the practice of massage on the behavior of mothers in massaging their own babies (Age 0-1 Years) in Baratan Village, Patrang District, Jember Regency. The research design used is True Experiment using Posttest Only Control Group Design. The population in this study was taken purposively, namely mothers with babies aged 0-1 years and their babies in Baratan Village, Patrang Subdistrict, Jember Regency with a total of 50 people and guidelines for determining the number of samples with Slovin's opinion in order to obtain a sample of 44 people. The sampling technique used is Simple Random Sampling. This research was conducted by assessing the mother's behavior in massaging the baby through a checklist. The results of this study were analyzed using Mc. Fan. The results of the analysis found that mothers who were given baby massage health education (27.3%) Yes, (72.7%) No. While mothers who were given health education and infant massage practice (68.2%) Yes and (31.8%) No. The results of the analysis showed a significant level of 0.05 was obtained (p = 0.002 <0.05) which showed that there was an effect of a combination of health education with the practice of massage on the mother's behavior in massaging her own baby (Age 0-1 Years). It is recommended for mothers to be more active and often ask health workers, especially in massaging babies so that the mother's behavior is better and right